(untitled) (International Journal of Food and Nutritional Sciences, 2024)
This study delves into the intricate relationship between sexual preference and personality traits among young adults aged 18-26 years. Through a comprehensive exploration, employing both quantitative and qualitative methodologies, we aim to discern potential correlations and influences. By administering standardized personality assessments and conducting in-depth examinations of survey questionnaires, we seek to unravel how individual sexual preferences intersect with various dimensions of personality. Insights from this research endeavor hold the promise of enriching our understanding of human sexuality and its nexus with personality, thereby contributing to the broader discourse on sexual orientation and psychological dynamics among emerging adults.